14th and 15th Century's Turkish Carpets with Animal Figures of Descriptive Survey of the Design and Color Features. (1st December 2016) - Genc, Mustafa; Kahraman, Mehmet Emin
Abstract: Starting from the first age, especially from palaeolithic and the stone ages, pictures drawn on thesurface of the inside of the caves, symbolic engravings done by sculpting stones using various tools, or equipmentsmade out of bones to be used in daily life, have been providing serious information about the history of humanity.The aim of this survey is the descriptive analysis of the engravings, especially the colors and designs of the carpets, from the 14 th and 15 th centuries. Ichographic and ichonologic analysis methods are used in this survey. The resultof the survey is that since the beginning of history of humanity, most important information and experiences onthe lives of people have been transferred by artistic activities, especially people transferred pain, sadness, happiness, and various messages to the next generations by weaving these emotions on carpets or rags.